Solve for a (complex solution)
\left\{\begin{matrix}\\a=-\frac{x}{3}\text{, }&\text{unconditionally}\\a\in \mathrm{C}\text{, }&x=4\end{matrix}\right.
Solve for a
\left\{\begin{matrix}\\a=-\frac{x}{3}\text{, }&\text{unconditionally}\\a\in \mathrm{R}\text{, }&x=4\end{matrix}\right.
Solve for x
x=-3a
x=4
Graph
Share
Copied to clipboard
x^{2}+3ax-4x-12a=0
Use the distributive property to multiply 3a-4 by x.
3ax-4x-12a=-x^{2}
Subtract x^{2} from both sides. Anything subtracted from zero gives its negation.
3ax-12a=-x^{2}+4x
Add 4x to both sides.
\left(3x-12\right)a=-x^{2}+4x
Combine all terms containing a.
\left(3x-12\right)a=4x-x^{2}
The equation is in standard form.
\frac{\left(3x-12\right)a}{3x-12}=\frac{x\left(4-x\right)}{3x-12}
Divide both sides by 3x-12.
a=\frac{x\left(4-x\right)}{3x-12}
Dividing by 3x-12 undoes the multiplication by 3x-12.
a=-\frac{x}{3}
Divide x\left(4-x\right) by 3x-12.
x^{2}+3ax-4x-12a=0
Use the distributive property to multiply 3a-4 by x.
3ax-4x-12a=-x^{2}
Subtract x^{2} from both sides. Anything subtracted from zero gives its negation.
3ax-12a=-x^{2}+4x
Add 4x to both sides.
\left(3x-12\right)a=-x^{2}+4x
Combine all terms containing a.
\left(3x-12\right)a=4x-x^{2}
The equation is in standard form.
\frac{\left(3x-12\right)a}{3x-12}=\frac{x\left(4-x\right)}{3x-12}
Divide both sides by 3x-12.
a=\frac{x\left(4-x\right)}{3x-12}
Dividing by 3x-12 undoes the multiplication by 3x-12.
a=-\frac{x}{3}
Divide x\left(4-x\right) by 3x-12.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}